Sondheim's A Little Night Music: Reconciling the comic and the sublime. Issue 2 (1st June 2014) - Wolfe, Graham
This article draws on Alenka Zupančič's and Slavoj Žižek's recent theorizations of comedy to examine Stephen Sondheim's highly successful 1973 musical A Little Night Music. Zupančič and Žižek argue that by 'looking awry' on popular modes like comedy we can explore how our relation to reality is still structured by fantasy and by passionate attachments to sublime objects – indeed, we can discover in comedy new modes of configuring the sublime. To explore A Little Night Music as a 'reconciliation' of comedy and sublimity is to open a consideration of Sondheim's contributions towards the very debates and deadlocks that Zupančič and Žižek identify and to suggest ways of extending their own psychoanalytic philosophy into the realms of musical theatre, a mode that they leave largely uninvestigated. In the process, the article aims to move beyond more traditional 'applications' of Lacanian psychoanalysis, arguing that Sondheim's musical encourages us to think differently about Lacanian theory per se and to look in new (and comic) ways at enigmatic terms like the 'Real'.